2015
DOI: 10.1074/jbc.m115.644179
|View full text |Cite
|
Sign up to set email alerts
|

An Early and Robust Activation of Caspases Heads Cells for a Regulated Form of Necrotic-like Cell Death

Abstract: Background: Caspase activation triggers apoptotic cell death. Results: Chelerythrine triggers necrotic-like cell death by an early and pronounced activation of caspases. Conclusion:The rate and level of caspase activation dictate whether cells die displaying apoptotic or necrotic features. Significance: Most antitumor drugs prompt concomitant apoptotic and necrotic morphological deaths; therefore understanding how the apoptosis-necrosis continuum occurs should shed light on anticancer treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…This option would also be compatible with a death mechanism that is less dependent on mitochondrial depolarization and promptly ends in necrosis. Moreover, the increase in caspase activity in necrotic processes has been previously described in other studies [126,127] and was linked to the presence of ROS, as observed in the present study. Furthermore, at least for the PS extract, our results might indicate the activation of both apoptosis and necrosis to induce cell death; one pathway would predominate, depending on each single case.…”
Section: Discussionsupporting
confidence: 91%
“…This option would also be compatible with a death mechanism that is less dependent on mitochondrial depolarization and promptly ends in necrosis. Moreover, the increase in caspase activity in necrotic processes has been previously described in other studies [126,127] and was linked to the presence of ROS, as observed in the present study. Furthermore, at least for the PS extract, our results might indicate the activation of both apoptosis and necrosis to induce cell death; one pathway would predominate, depending on each single case.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a high number of caspase-3 positive cells was observed 5 h after irradiation, which is traditionally considered an event exclusively associated with apoptosis. A recent study has demonstrated that the treatment of human-derived neuroblastoma cells with chelerythrine triggered a regulated form of necrotic cell death induced by an increase of ROS levels, which elicited an overactivation of caspases, caspase-3 included18. Given that PDT induces the formation of ROS, it is possible that a similar caspase-3 activation occurred under our experimental conditions.…”
Section: Discussionmentioning
confidence: 75%
“…C). Like TRAIL, albeit to a higher extend, NV10 and NV100 were found to induce postapoptotic necrosis (Garcia‐Belinchon et al, ; Rogers et al, ). Importantly, however, NPs at the corresponding iron oxide concentrations were unable to trigger apoptosis in these cells (NP10: 8.9%; NP100: 13%; and control not stimulated (CTL): 9.7%).…”
Section: Resultsmentioning
confidence: 99%